McGill Oximetry Score to Predict Risk of Obstructive Sleep Apnea in Pediatric Patients - Wing-Shan Chan; Eric Yat-Tung Chan; Daniel Kwok-Keung Ng; Ka-Li Kwok; Ada Yuen-Fong Yip; Shuk-Yu Leung (Pediatric Respirology and Critical Care Medicine)
Objective: The aim of this study is to investigate the use of overnight oximetry to predict high Apnea–Hypopnea Index (AHI) in Hong Kong children with habitual snoring. Methodology: We have retrospectively analyzed the polysomnography (PSG) of 573 patients with habitual snoring with age ranged from 6 months to 18 years old. Patients with syndromal diagnosis or neuromuscular disorders were excluded from the study. The sensitivity, specificity, positive predictive value, and negative predictive value (NPV) of oximetry to predict AHI were calculated. Results: McGill score >1 had high specificity 99.07% and low sensitivity 16.81% to detect AHI >1. SpO2 nadir <95% has high sensitivity 98.56% and NPV 97.56% to predict AHI >5. Conclusion: The use of the McGill score together with nadir SpO2 in overnight oximetry can help in stratifying the severity of obstructive sleep Apnea and thus prioritizing PSG testing.